2014
DOI: 10.1111/edt.12135
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical and radiographic follow up of subluxated and intruded maxillary primary anterior teeth

Abstract: For both intrusion and subluxation, trauma sequelae were diagnosed even after the 3-4 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 28 publications
4
43
0
1
Order By: Relevance
“…It is particularly important when designing the optimum follow‐up programme to consider the risk of serious complications as well as the expected time of diagnosis. A previous study analysing the time of diagnosis found that most complications were diagnosed within the first 6‐12 months and 1‐2 years after the injury . However, many of the patients in that study were irregular follow‐up attenders, and the time of diagnosis may therefore vary from the actual time at which the healing complication occurred.…”
Section: Discussionmentioning
confidence: 93%
“…It is particularly important when designing the optimum follow‐up programme to consider the risk of serious complications as well as the expected time of diagnosis. A previous study analysing the time of diagnosis found that most complications were diagnosed within the first 6‐12 months and 1‐2 years after the injury . However, many of the patients in that study were irregular follow‐up attenders, and the time of diagnosis may therefore vary from the actual time at which the healing complication occurred.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study analysing the time of diagnosis of complications found that most cases were diagnosed within the first 6-12 months and 1-2 years after the injury. 25 However, many of the patients in that study were irregular follow-up attenders, and the time of diagnosis may therefore vary much from the actual time at which the healing complication occurred. A study by Cardoso et al 26 reported that most serious complications were diagnosed be- The risk of serious complications such as PN and infection with periapical inflammation and IRR was moderate among teeth with lateral luxation that were left without further treatment or teeth with extrusion that were repositioned.…”
Section: Discussionmentioning
confidence: 95%
“…This would both have time and economic benefits, but the method needs to be tested further. The teeth to be selected would be traumatized or externally injured (by attrition, caries or operative procedures) and/or physiologically aged teeth (Andreasen & Kahler 2015, Qassem et al 2015. The latter may be a more frequent occurrence, as population data show a marked decrease in the number of extracted teeth, indicating that people retain their teeth until an older age (Bjørndal 2011, Demant et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The canal system may partly or completely obliterate as a consequence of physiological ageing and/or external injuries, such as attrition, caries, previous operative procedures, as well as trauma (Andreasen & Kahler 2015, Qassem et al 2015. Root canal treat-ment is only advocated when apical periodontitis develops (Robertson et al 1996) or with signs such as tenderness to percussion, PAI scores ≥3 and a negative response to sensibility testing (Oginni et al 2009).…”
Section: Introductionmentioning
confidence: 99%